CHARACTERIZATION AND EVALUATION OF MUSA ACUMINATA CULTIVARS IN INDONESIA BASED ON MICROSATELLITE MARKERS - Amin Retnoningsih; Rita Megia; Alex Hartana (PTTI, 2010)
Amin Retnoningsih, Rita Megia & Alex Hartana. 2010. Characterization and Evaluation of Musa acuminata Cultivars in Indonesia Based on Microsatellite Markers. Floribunda 4(1): 21–32. — Difficulties in identifying Musa acuminata cultivars are caused by their large variations, numerous names and synonyms. The morphological characters provide limited information, therefore identifying cultivars could be difficult. In line with the difficulty to identify the cultivars, thus this study was aimed to verify taxonomic status, to identify and to reveal genetic relationships among banana accessions based on microsatellite markers. The DNA of 59 banana accessions which have morphologically been classified into AA and AAA genomic groups was analyzed using 12 primers. The results showed that only 8 primers producing discrete and repeatable alleles. The number of alleles per primer ranged from 5 for the MaCIR327b to 15 for the MaCIR108 and the Ma-1-139. The largest three of the MaCIR108 alleles included in length range of the B genomic alleles, whereas the other 12 alleles fell into length range of the A genomic alleles. Hence, the 11 accessions having alleles of the A and B genomes have been incorrectly classified into M. acuminata cultivars. They should be placed in hybrids species M. x paradisiaca. Forty eight accessions studied neither exhibited status change, nor possessed specific alleles to distinguish between AA and AAA genomic groups. Difficulties in separating AA from AAA may also as a result of the dosage effects of a microsatellite allele. Therefore, the accessions having maximum 2 alleles in each primer should be designated as AA or AAA genomic group. Due to the presence of 6 identical genotypes consisting of 12 accessions, there were detected only 42 genotypes resulted from analysis of the 48 accessions using the 8 primers. Genetic relationship analysis showed that genomic groups of those pure acuminata cultivars could not be differentiated significantly, though most of them tend to be clustered according to ploidy level.